2000
DOI: 10.1136/ard.59.9.705
|View full text |Cite
|
Sign up to set email alerts
|

Retinal disease in patients with systemic lupus erythematosus

Abstract: Objective-To investigate the incidence of retinopathy in systemic lupus erythematosus (SLE) and to clarify its significance in relation to other clinical manifestations. Methods-A cross sectional study on lupus retinopathy was made in 69 patients with SLE. One expert ophthalmologist examined the ocular fundi of the lupus patients without any information of their disease state. Clinical and laboratory findings in the patients with retinopathy and those without were compared. Results-Retinopathy was found in 7/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 11 publications
4
97
0
3
Order By: Relevance
“…16 Retinal lesions seen in the latter differ from those in the former, consisting mainly of cotton wool spots or haemorrhages and were related to the presence of antiphospholipid antibodies and central nervous system disease. The difference in the retinal findings between the two diseases may reflect the difference in features of vascular damage characteristic of each disease.…”
Section: Discussionmentioning
confidence: 96%
“…16 Retinal lesions seen in the latter differ from those in the former, consisting mainly of cotton wool spots or haemorrhages and were related to the presence of antiphospholipid antibodies and central nervous system disease. The difference in the retinal findings between the two diseases may reflect the difference in features of vascular damage characteristic of each disease.…”
Section: Discussionmentioning
confidence: 96%
“…This finding may be due to the different dynamic ranges between the two techniques (standard automated perimetry 0–40 dB vs. fundus perimetry 0–20 dB): slight reductions in sensitivity, exceeding 20 dB, in the central visual field may remain undetected on fundus perimetry. Interestingly, Ushiyama et al [52] reported an association between retinopathy revealed at fundus examination and serum creatinine levels in SLE patients. In our SLE population, no significant correlation occurred between creatinine levels and ophthalmological findings probably because of the small sample size as well as the different inclusion criteria used.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible mechanisms for the development of lupus retinopathy. In some patients, the manifestations are associated with complementdependent vasculitis, while in others, they are associated with anti-phospholipid antibodies (1)(2)(3)(4). Abnormalserum levels of several cytokines in SLEhave been reported in addition to abnormalities of spontaneous or stimulated cytokine production by peripheral blood mononuclear cells in vitro.…”
Section: Introductionmentioning
confidence: 99%